2004
DOI: 10.17305/bjbms.2004.3460
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of neonatal BCG vaccines against tuberculous meningitis

Abstract: Neonatal BCG vaccination reduces the risk of tuberculosis and provides protection higher than 80% against the development of meningeal and miliary tuberculosis in newborns. Tuberculosis meningitis remains a major problem and also an important cause of death in some countries. In countries with high and moderate incidence of tuberculosis, prevention from the most severe complications of tuberculosis can be achieved only with a high coverage of the universal BCG neonatal immunization, being higher than 98% in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Currently, BCG vaccination covers 85% of newborn infants, and it has been estimated that nearly 100 million children are vaccinated with BCG vaccine every year (12). Several studies have shown that BCG protects against TBM and that its efficacy is around 75 to 85% (8,18,27,34,105,129,163,188,194,212,244,248). Two recent meta-analyses also concluded that BCG vaccination protects against TBM (39,175).…”
Section: Preventionmentioning
confidence: 99%
“…Currently, BCG vaccination covers 85% of newborn infants, and it has been estimated that nearly 100 million children are vaccinated with BCG vaccine every year (12). Several studies have shown that BCG protects against TBM and that its efficacy is around 75 to 85% (8,18,27,34,105,129,163,188,194,212,244,248). Two recent meta-analyses also concluded that BCG vaccination protects against TBM (39,175).…”
Section: Preventionmentioning
confidence: 99%
“…Those factors could be understood as reflecting a type of individual-susceptible immunity. Generally, BCG vaccination policies aim to achieve a protective effect against tuberculosis at birth or during childhood [ 13 ], and it has been reported that BCG vaccination has a protective effect on all-cause mortality, yellow fever, and influenza [ 14 ]. It has been proposed that BCG vaccination has a protective effect against COVID-19 because BCG contains a 9-amino-acid sequence similar to that of SARS-CoV-2 [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The severe forms of TB, such as milliary TB and TBM in children, can probably be prevented by the BCG (Bacillus Calmette-Guérin) vaccine. Several studies have indicated the protective effects of the BCG vaccine against TBM (Awasthi and Moin, 1999;Puvacic et al, 2004;Mittal et al, 1996;Trunz et al, 2006;Xiong et al, 2009). A protective efficacy of approximately 60-70% for the BCG vaccine against TBM has been reported (Thilothammal et al, 1996;Chavalittamrong et al, 1986).…”
Section: Treatments and Management Of Tbmmentioning
confidence: 99%